(untitled) (AYUSHDHARA, 2024)
"Rooted in ancient Indian wisdom, Ayurveda, a holistic science of life, offers a unique approach to health and wellness through natural therapies and herbal remedies. Emphasizing individualized treatment, Ayurveda aims to balance the body’s three fundamental energies (Vata, Pitta, Kapha) for optimal health and disease prevention." Psoriasis, known as Eka Kustha in Ayurveda, is a chronic autoimmune disorder characterized by hyperproliferation of the skin cells, leading to erythematous, scaly plaques that cause discomfort and affect patient’s quality of life. From an Ayurvedic perspective, Eka Kustha is associated with imbalances in the Vata and Kapha doshas, as well as impurity in blood (Rakta dhatu) and aggravated toxins (Ama). Bhringaraja is praised for its multiple therapeutic properties, including balancing Kapha and Vata, promoting hair health, treating skin diseases like psoriasis, and offering general rejuvenation and strengthening benefits. It is recognized as a powerful herb in traditional Ayurvedic medicine. Present case report, A 52yrs old male patient presented with scaling, itching all over body predominantly upper and lower back for 8 months. The patient was treated with Bhringraja (Eclipta alba Hassk.) churna for period of 45 days, Patient got significant improvement after 45 days. The patient showed significant improvement in PASI score and quality of life with no adverse effects. The treatment protocol adopted based on the Ayurvedic principles, targeting the Vatakapha dosha predominance in Ekakusta. This case report highlights the effectiveness of Shamana oushadi in managing psoriasis and support further research to explore its potential as a complementary therapy.